Pengaruh Keteladanan Guru Akidah Akhlak Terhadap Perilaku Agresi - Permadi, Aji; Bahrodin , Ariga (ILJ: Islamic Learning Journal, 2025)
In this age of globalization, many psychological problems or mental illnesses arise among adolescents and cause bad social changes. Many mistakes about the characteristics of adolescents who are still in the process of developing are related to their negative behavior, such as smoking, drinking alcohol, brawls, and so on. Therefore it is important for teachers to educate students to minimize aggression behavior. The purpose of this study was to determine whether there is an effect of exemplary Akidah Akhlak Teacher on Aggression Behavior in Students at MA Darul Faizin Catak Gayam Mojowarno Jombang. This study used a quantitative approach with a survey method. the research sample was 89 class XII students at MA Darul Faizin Catak Gayam Mojowarno Jombang who were selected using cluster random sampling technique. The data collection instrument was a questionnaire, which was validated and tested for reliability. Data analysis using descriptive and inferential statistics with the Spearman correlation test. The results showed that there was an influence between the exemplary moral akidah teacher and aggression behavior, this is known from the level correlation test (rank spearman) conducted by researchers by getting a significance value of 0.016 which is smaller than 0.05. By referring to the basis for decision making if the significance value is smaller than 0.05, there is an influence between variable x and also variable y. However, if the greater the significance value, the greater the significance value. However, if the significance value is greater, there is no influence between the x variable and the y variable. In addition, the coefficient number is known to be obtained at 0.254, which means that it is positive, which means that there is a unidirectional relationship, if X increases and Y also increases, and the coefficient classification is at a low level of strength / relationship